2012
DOI: 10.1038/nn.3022
|View full text |Cite
|
Sign up to set email alerts
|

SK channel modulation rescues striatal plasticity and control over habit in cannabinoid tolerance

Abstract: Endocannabinoids (eCBs) regulate neuronal activity in the dorso-lateral striatum (DLS), a brain region that is involved in habitual behaviors. How synaptic eCB signaling contributes to habitual behaviors under physiological and pathological conditions remains unclear. Using a mouse model of cannabinoid tolerance, we found that persistent activation of the eCB pathway impaired eCB-mediated long-term depression (LTD) and synaptic depotentiation in the DLS. The loss of eCB LTD, occurring preferentially at cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
123
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 48 publications
2
123
0
Order By: Relevance
“…The ability of nervous systems, and their states, to be changed in this way is called plasticity; and plasticity generalizes across functioning nervous systems (e.g., Fu et al 2002;Jacob et al 2007;Cassenaer & Laurent 2007;Yin et al 2009;Nazzaro et al 2012;Smith & Graybiel 2013;Arce--McShane et al 2014). Nervous systems, and their subsystems, are 'plastic' in the sense that their proper functioning throughout daily life involves changes in the probability subsequent activities will occur (e.g., Dan & Poo 2006;McMahon & Leopold 2012;Veniero et al 2013).…”
Section: The Wild Coincidence Objection: An Empirical Objection Withomentioning
confidence: 99%
“…The ability of nervous systems, and their states, to be changed in this way is called plasticity; and plasticity generalizes across functioning nervous systems (e.g., Fu et al 2002;Jacob et al 2007;Cassenaer & Laurent 2007;Yin et al 2009;Nazzaro et al 2012;Smith & Graybiel 2013;Arce--McShane et al 2014). Nervous systems, and their subsystems, are 'plastic' in the sense that their proper functioning throughout daily life involves changes in the probability subsequent activities will occur (e.g., Dan & Poo 2006;McMahon & Leopold 2012;Veniero et al 2013).…”
Section: The Wild Coincidence Objection: An Empirical Objection Withomentioning
confidence: 99%
“…This correlates with drug-induced changes in synaptic functions (LTP, LTD) in the dorsal striatum (Gerdeman et al, 2003) and possibly agrees with chronic stimulant treatment-induced changes in the sensitization of behavioral stereotypy and striosomal early gene activation in the lateral striatum (Canales and Graybiel, 2000;. In THCdependent mice that show no difference in responding to valued versus devalued rewards, bilateral infusion of apamin (a SK Ca channel blocker) into the dorsolateral striatum rescued the eCB-dependent LTD (lost during tolerance development) for up to 5 days and changed the behavior from habitual responding to goal-directed responding with a significantly greater responding for valued than devalued rewards (Nazzaro et al, 2012). D 1 R activation (D 1 R-like) has been linked to LTP and D 2 R activation (D 2 R-like) to LTD in MSN glutamate synapses (Calabresi et al, 2007).…”
Section: Drug-induced Neuroplasticitymentioning
confidence: 99%
“…Also, similar to the NAc (ventral striatum), LTD of cortical glutamatergic inputs to the dorsal www.perspectivesinmedicine.org striatum is dependent on endocannabinoid activation of presynaptic CB1 receptors (Gerdeman et al 2002;Ronesi et al 2004), which may be involved in the establishment of striatal-dependent learning and habit formation (Kano et al 2009). Because of the importance of the endogenous cannabinoid system in mediating motor behavior, instrumental learning, and habit formation and its potential involvement in compulsive drug seeking, the role of THC in regulating endogenous cannabinoid function has been studied (Nazzaro et al 2012). This study found that, similar to previous work in other brain areas, treatment of mice with THC (10 mg/kg, i.p., 5 d) eliminated endogenous cannabinoid-dependent LTD of cortical inputs to MSNs in the dorsolateral striatum that was associated with behavioral tolerance to THC (Nazzaro et al 2012).…”
Section: Dorsal Striatummentioning
confidence: 99%
“…Because of the importance of the endogenous cannabinoid system in mediating motor behavior, instrumental learning, and habit formation and its potential involvement in compulsive drug seeking, the role of THC in regulating endogenous cannabinoid function has been studied (Nazzaro et al 2012). This study found that, similar to previous work in other brain areas, treatment of mice with THC (10 mg/kg, i.p., 5 d) eliminated endogenous cannabinoid-dependent LTD of cortical inputs to MSNs in the dorsolateral striatum that was associated with behavioral tolerance to THC (Nazzaro et al 2012). Striatal MSNs send their GABAergic output to downstream targets via two pathways known as indirect and direct, which are defined by various postsynaptically expressed receptors and neuropeptides (Kreitzer 2009).…”
Section: Dorsal Striatummentioning
confidence: 99%
See 1 more Smart Citation